A Comparison of Emergency Preparedness Policies by Long-Term Care Setting Type in Ohio: Assisted Living Settings Lag Behind Nursing Homes in Key Areas. (April 2021) - Kennedy, Katherine A.; Hua, Cassandra L.; Nelson, Ian
Skilled nursing facilities (SNFs) have received regulatory attention in relation to their emergency preparedness. Yet, assisted living settings (ALs) have not experienced such interest due to their classification as a state-regulated, home- and community-based service. However, the growth in the number of ALs and increased resident acuity levels suggest that existing disaster preparedness policies, and therefore, plans, lag behind those of SNFs. We examined differences in emergency preparedness policies between Ohio's SNFs and ALs. Data were drawn from the 2015 wave of the Ohio Biennial Survey of Long-Term Care Facilities. Across setting types, most aspects of preparedness were similar, such as written plans, specifications for evacuation, emergency drills, communication procedures, and preparations for expected hazards. Despite these similarities, we found SNFs were more prepared than large ALs in some key areas, most notably being more likely to have a backup generator and 7 days of pharmacy stocks and generator fuel.